RELATIONSHIP OF NUTRITIONAL ANEMIA WITH THE EVENT OF WORM INFECTION IN PRIMARY SCHOOL CHILDREN IN THE WORK AREA OF AIR BILITI PUSKESMAS MUSI RAWAS - Silvia Rahmi; Charil Anwar; Hamzah Hasyim (University of Sultan Ageng Tirtayasa, 2021)
More than 1.5 billion people or 24% of the world's population experience worm infections that are transmitted through the soil. Worm infections that occur can damage the nutritional status in the form of anemia in all children, especially school age. The purpose of this study was to determine the relationship between nutritional anemia and the incidence of helminthiasis. This research method is an analytical observational with a cross-sectional design. The population in the study was conducted on elementary school children in the working area of the Air Biliti Health Center, Musi Rawas Regency in 2021. The sample in this study was 98 with simple random sampling at five schools in the working area of the Air Biliti Health Center. The study was conducted in March 2021. The results of this study showed that most of the proportions of negative helminth infections were 60 (61.2%), not anemic 71 (72.4%), Class VI 39 (39.8%), 11 years old 32 (32,7 % ), female 50 (51.0%), high parental education 53 (54.1%), farmer occupation 61 (62.2%), income 50 (51.0%). The results of the analysis of the significant relationship between nutritional anemia (p value 0.000, OR = 6.500) and infection rates in elementary school-aged children in the work area of Air Biliti Health Center, Musi Rawas Regency. Based on the results of the study, it was found that the importance of maintaining environmental cleanliness and personal hygiene, coupled with the habit of taking a worm medicine and attention from parents to reduce helminth infections that cause children to experience nutritional anemia.